1985
DOI: 10.1111/j.1365-2648.1985.tb00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Authority and responsibility delegation predicts quality of care

Abstract: This study, conducted in acute care hospitals, supports and expands previous findings that delegation of responsibility and authority in the nursing service hierarchy is related to known factors affecting quality of patient care. Quality health care is improved if staff nurses are given autonomy and are expected to function at the level for which they have been prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The staff nurses in Simpson's (1985) study perceived more authority than responsibility but, as she points out, given that acceptance of delegated responsibility depends on the receptiveness of subordinates, the staff nurses were perhaps not accepting the responsibility delegated to them. This in turn may have resulted in their perception of less responsibility than was actually delegated.…”
Section: Authoritymentioning
confidence: 90%
See 1 more Smart Citation
“…The staff nurses in Simpson's (1985) study perceived more authority than responsibility but, as she points out, given that acceptance of delegated responsibility depends on the receptiveness of subordinates, the staff nurses were perhaps not accepting the responsibility delegated to them. This in turn may have resulted in their perception of less responsibility than was actually delegated.…”
Section: Authoritymentioning
confidence: 90%
“…Failure to delegate may result in the nurse being overburdened by work, the quality of patient care could be compromised and other staff may begin to feel frustrated at the lack of opportunity for further development. Simpson (1985) in a survey of four acute care hospitals in San Francisco measured job satisfaction, staff turnover and absenteeism in relation to staff's perceived delegation of responsibility and authority in the nursing service hierarchy. It was found that when nurses were given more responsibility and concomitant authority by the administration they experienced more job satisfaction, absentee-ism and staff turnover were reduced and the quality of care appeared to be improved.…”
Section: Accepted For Publication: 8 July 1993mentioning
confidence: 99%
“…This hierarchical structure dissipates authority; as a result, the degree of accountability is limited to the degree of authority vested in the individual nurse (Pearson). Finally, research has shown that when nurses are given more responsibility and authority by administration, they report higher levels of job satisfaction, a decrease in job absenteeism and staff turnover, and improved quality of care (Simpson, 1985;Curry, Wakefield, Price, Mueller & McCloskey, 1985). It is readily apparent that through de-centraliztion of authority in the structure of employing institutions, nurses will be able to develop as autonomous, accountable practitioners, and will have more job satisfaction, resulting in an enhanced quality of healthcare delivery.…”
Section: For What Should Nurses Be Held Accountable?mentioning
confidence: 99%
“…Never before has it been more critical to prepare professional nurses who are autonomous, assertive, accountable practitioners who communicate effectively, accept leadership roles and possess management competencies in new practice arenas. 1–4 …”
Section: Introductionmentioning
confidence: 99%
“…Never before has it been more critical to prepare professional nurses who are autonomous, assertive, accountable practitioners who communicate effectively, accept leadership roles and possess management competencies in new practice arenas. [1][2][3][4] Since the mid-80s, our society has confronted and begun to address more intensively the challenge of pro-viding quality health-care services for chronically ill patients, mainly the elderly, in acute-care settings, in longterm care (LTC) hospitals and in a variety of community settings.The long-term care industry is rapidly expanding into subacute care. At the same time, length of stay in acute care hospitals has decreased and patient acuity has increased.The data represent continuous movement of the elderly among acute, long-term and home-care settings.…”
Section: Introductionmentioning
confidence: 99%